Customer and hospitality service-provider dramas: Stories, experiential learning exercises, and deep assessment - Woodside, Arch; Chen, P.; De Villiers, R.; Huan, T. (2017)
Copyright © 2018 by Emerald Publishing Limited. This chapter is the introduction to the 26 trade-tale case studies in the present volume. Face-to-face, telephone, and written interactions between salespersons and customers and service-providers and customers occur frequently in everyday life. Successful communications and outcomes are likely to occur for the majority of these encounters. However, most customers, salespersons, and service-providers are likely to be able to identify personal examples of miscommunications and bad outcomes. Most of the trade-tale cases in this volume include in-depth cases of miscommunications and bad outcomes. Chapter 1 is a call for achieving "requisite variety" and in-depth examination of such cases. All the cases in this volume present deep dives into describing and understanding details in the inter action processes and alternative versus actual outcomes of each case study. The numerous and varied case studies along with the deep interpretations of the processes and outcomes provide useful steps for achieving the objective of requisite variety. Chapter 1 provides details of the topics and coverage of requisite variety.